The combination of RNA-seq transcriptomics and data-independent acquisition proteomics reveals the mechanisms underlying enhanced salt tolerance by the ZmPDI gene in Zoysia matrella [L.] Merr. - Ming, Qiang; Wang, Kai; Wang, Jingjing; Liu, Jianxiu; Li, Xiaohui; Wei, Peipei; Guo, Hailin; Chen, Jingbo; Zong, Junqin (Frontiers in Plant Science, 2022)
Zoysia matrella [L.] Merr. is one of the three most economically important Zoysia species due to its strong salt tolerance and wide application. However, the molecular mechanisms regulating salt tolerance in Z. matrella remain unknown. The protein disulfide isomerase ZmPDI of Z. matrella was obtained by salt stress screening with yeast cells, and its expression was significantly upregulated after salt stress. Based on the obtained ZmPDI overexpression transgenic Z. matrella plants, we carried out salt tolerance identification and found that ZmPDI can significantly enhance the salt tolerance of Z. matrella. Root samples of OX-ZmPDI transgenic and wild-type plants were collected at 0 and 24 h after salt treatments for RNA-seq and data-independent acquisition (DIA) proteome sequencing. Combined analysis of the transcriptome and proteome revealed that ZmPDI may enhance the salt tolerance of Z. matrella by regulating TUBB2, PXG4, PLDα2, PFK4 and 4CL1. This research presents the molecular regulatory mechanism of the ZmPDI gene in Z. matrella for resistance to salt stress and facilitates the use of molecular breeding to improve the salt tolerance of grasses.